Sistem Hukum Dalam Mengembalikan Kerugian Keuangan Negara Dari Hasil Tindak Pidana Korupsi Dalam Perspektif Peraturan Perundang-Undangan Di Indonesia - Tumbur Ompu Sunggu (Yuriska: Jurnal Ilmiah Hukum, 2025)
Background Corruption has become a very dangerous problem for all countries in the world, including Indonesia. According to data compiled by Transparency International in 2022, Indonesia ranked 110th out of 180 countries, with a score of 34. Therefore, it is crucial for a country to establish efficient procedures, especially for the recovery of state financial losses caused by corruption. This study examines the mechanism for recovering state financial losses due to corruption from a legal perspective in Indonesia. This study aims to analyze the regulations for recovering state losses due to corruption in Indonesia in accordance with statutory provisions. This study uses various methodologies, including conceptual frameworks, legal analysis, case studies, and normative legal research. Emphasis is placed on the process of restitution of state losses in accordance with legal provisions, as well as the difficulties in handling corruption. The results show that the application of restorative justice in corruption cases can reduce the burden on the state budget because it eliminates the need to process and cover the costs of treatment for detained or convicted perpetrators of corruption. However, the findings of this study also show that there is a discrepancy with Article 4 of Law Number 31 of 1999, which states that the return of state financial or state economic losses does not eliminate criminal penalties for perpetrators of criminal acts as referred to in Article 2 and Article 3. Research Metodes : In this research, the author uses a normative legal research method (normative juridical) Findings: The return of state financial losses is an effort by the state against the perpetrators of corruption to return the state's financial losses that have been corrupted, the amount of which is equal to the amount of money that was corrupted by the perpetrator according to the audit results, where if the perpetrator does not have the same value of money as what he took, the state will confiscate the assets or property belonging to the perpetrator whose value is equal to the amount of money that was corrupted. However, in the field, investigators and prosecutors are often overwhelmed in confiscating assets from the perpetrator, because the perpetrator tries to hide his assets so that they are not confiscated by the state by laundering money where the assets are changed to the name of another person, so that investigators and prosecutors in this case the prosecutor's office as the executor are hampered. Therefore, there must be quick and accurate action from investigators and prosecutors to be able to examine all distribution of money from the perpetrator in order to find out if there are suspicious transactions and to examine all those who received transactions from the perpetrator. Conclution: Corruption is a criminal act that is very detrimental to the State for personal or group interests. The consequences of corruption cause a State's economy to be paralyzed and can damage the order of a State, especially with a large number, considering that there are still many Indonesian people who are financially disadvantaged so they need a touch from the government in the form of social assistance, so there needs to be firm, fast and accurate action from authorized officials in this case the Corruption Eradication Commission, the Prosecutor's Office and the Police to return the State's financial losses by confiscating the perpetrator's assets with a value equal to the amount of money they embezzled, before the perpetrator launders money by changing the name of his assets to another person's name to avoid confiscation by authorized State officials.